An educational kit to teach and learn Operational Amplifiers - Costa, Ricardo J. (2018)
Operational Amplifiers are widely used for implementing simple and complex electronic circuits in electronic engineering. As a contribution to improve the way this integrated circuit is included in electronic engineering courses’ curricula, this paper presents a prototype of an educational kit comprising a simulation tool and a reconfigurable hardware platform with the OpAmp uA741. It enables the simulation and experimentation